2021
DOI: 10.1039/d0en00992j
|View full text |Cite
|
Sign up to set email alerts
|

Natural organic matter facilitates formation and microbial methylation of mercury selenide nanoparticles

Abstract: Tiemannite nanoparticles available for microbial mercury methylation are formed during the co-precipitation of natural organic matter, divalent mercury and selenium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…2b and S7 †) both exceeded the maximum K q for diffusion-controlled quenching (2.0 × 10 10 L mol −1 s −1 ), 24,26 indicating the occurrence of a static quenching process that may involve EPS-Hg(II) inner-sphere complexation. 47,48 The Stern-Volmer quenching constants (K SV ), and binding constants (K A ) of EPS(ND132)-Hg were consistently larger than those of EPS(PCA)-Hg, suggesting a stronger binding affinity of EPS(ND132) to Hg(II) relative to EPS(PCA) (Fig. 2b and S7 †).…”
Section: Inner-sphere Complexation Between Eps and Hg(ii)mentioning
confidence: 99%
“…2b and S7 †) both exceeded the maximum K q for diffusion-controlled quenching (2.0 × 10 10 L mol −1 s −1 ), 24,26 indicating the occurrence of a static quenching process that may involve EPS-Hg(II) inner-sphere complexation. 47,48 The Stern-Volmer quenching constants (K SV ), and binding constants (K A ) of EPS(ND132)-Hg were consistently larger than those of EPS(PCA)-Hg, suggesting a stronger binding affinity of EPS(ND132) to Hg(II) relative to EPS(PCA) (Fig. 2b and S7 †).…”
Section: Inner-sphere Complexation Between Eps and Hg(ii)mentioning
confidence: 99%
“… Nano-Enhanced Formulations: By adding nanofertilizers to traditional fertilisers or soil amendments, their overall effectiveness may be increased and their risk of side effects can be decreased [ 180 ]. Organic matter or soil amendments: This improves the interactions of nanofertilizers with soil elements, enhancing nutrient retention and availability [ 181 ]. Targeted Delivery: Enhancing nutrient absorption and minimizing loss may be accomplished by using nanocarriers or nanoparticles that can be directed to certain plant tissues or root zones [ 182 ].…”
Section: Applications Of Nanomaterials In Biocontrol and Plant Growth...mentioning
confidence: 99%
“…Organic matter or soil amendments: This improves the interactions of nanofertilizers with soil elements, enhancing nutrient retention and availability [ 181 ].…”
Section: Applications Of Nanomaterials In Biocontrol and Plant Growth...mentioning
confidence: 99%
“…NOM exhibits a strong affinity for Hg and forms Hg–NOM complexes via various functional groups present in NOM, such as thiol (–SH), carboxyl (–COOH), and amine moieties (–NH 2 ). 19,20 Such complexation could further influence the chemical speciation, transformation, and bioavailability of Hg, 21,22 The presence of NOM can have diverse effects on Hg removal processes, and previous studies have reported varying observations regarding its effects. For instance, it has been reported that NOM can compete with sorption sites for Hg complexation, leading to a decline in the adsorption capacity of nanomaterials such as FeS, 2 thiolated graphene oxide, 20 activated carbon, 23 and zero valent iron.…”
Section: Introductionmentioning
confidence: 99%